2015
DOI: 10.1371/journal.pone.0132287
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection Burden of Hepatitis C Virus and Human Immunodeficiency Virus among Injecting Heroin Users at the Kenyan Coast

Abstract: BackgroundInjection drug use is steadily rising in Kenya. We assessed the prevalence of both human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) infections among injecting heroin users (IHUs) at the Kenyan Coast.MethodsA total of 186 IHUs (mean age, 33 years) from the Omari rehabilitation center program in Malindi were consented and screened for HIV-1 and HCV by serology and PCR and their CD4 T-cells enumerated by FACS.ResultsPrevalence of HIV-1 was 87.5%, that of HCV was 16.4%, co-infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…The IDU population, although small, shows a higher proportion of HCV mono-infections (93%) and HCV/HIV co-infection (72%). This finding is consistent with previous studies in Kenya 29 , 46 and elsewhere. 56 , 57 The use of unsafe injection practices has been linked with HCV and HIV infections among drug users.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The IDU population, although small, shows a higher proportion of HCV mono-infections (93%) and HCV/HIV co-infection (72%). This finding is consistent with previous studies in Kenya 29 , 46 and elsewhere. 56 , 57 The use of unsafe injection practices has been linked with HCV and HIV infections among drug users.…”
Section: Discussionsupporting
confidence: 94%
“… 14 Anti-HCV prevalence among blood donors in Nairobi was 1.8%, 15 whereas among outpatients from three hospitals, an HBV surface antigen (HBsAg) positivity of 11.4% was documented. 28 An HIV prevalence of 18.7% was reported among IDUs in Nairobi 7 and 87.5% among injecting heroin users at the Kenyan coast, 29 whereas an HCV prevalence of 16.4% and HCV/HIV co-infection prevalence of 17.9% among the same heroin users was documented. 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A HCV prevalence of 14% among the HIV infected was demonstrated. Previous studies from selected population groups have shown that HCV prevalence ranges from 0.7 % to 0.9 % among blood donors; 3.9% among patients with symptoms of liver disease (Ochwoto et al, 2016); 1.0% (Chen et al, 2011;Harania et al, 2008); 22% and 16, 4% among IDUs (Mwatelah et al, 2015;Muasya et al, 2008); 0.76 among informal settlements (Kerubo et al, 2015).The findings of the current study seems consistent with that of High risk population group like IDUs . This is quite informative, since in Kenya, the assumptions have been HCV is mostly higher among most at risk populations.…”
Section: Discussionsupporting
confidence: 89%
“…Hepatitis C patients were found to be illiterate, it shows that lack of knowledge about the disease and its precautions become a strong cause for disease. In this study, there is an increase of HCV infection as compared to the study which was done by Sacks-Davis R 17 in the entire Coast which showed a prevalence of 16.7%.We have shown that there is increased diversity along the coastal strip centers like Mtwapa which is part of Kilifi town both are under Muslim welfare association (MEWA).…”
Section: Discussionmentioning
confidence: 47%